Genetic parameters and correlations associated with the selection of kale clones via REML/BLUP estimates - Eduardo Alves da Silva; Ariana Lemes da Costa; Orlando Gonçalves Brito; Valter Carvalho de Andrade Junior; André Boscolo Nogueira da Gama; Sebastião Márcio de Azevedo (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to estimate the genetic parameters and correlations of characteristics related to production and color in kale and to select the best genotypes based on REML/BLUP estimates. The experiment was carried out in a completely randomized block design, with three replicates. The treatments consisted of 34 experimental kale clones. The parameters evaluated were: total leaf yield (TLY), number of commercial leaves (NCL), average leaf mass (ALM), number of shoots (NS), chlorophyll content (CC), and colorimetric patterns of luminosity (L), chroma (C), and hue (h) of the leaves. Genetic parameters, genotypic and phenotypic correlations, and genetic values were estimated. The kale genotypes UFLA 06, UFLA 14, UFLA 16, UFLA 22, and UFLA 34 have good productive characteristics and intense green color, with high heritability. The characteristics TLY, NCL, ALM, NS, CC, and colorimetric patterns of L and C present high heritability in kale. TLY shows a positive correlation with the NCL and the ALM in kale. The genotypes UFLA 02, UFLA 04, UFLA 13, UFLA 25, UFLA 31, and UFLA 32 stand out for their productive characteristics, but not in high levels of antioxidants. The NCL presents positive correlation with the NS, which does not benefit seed production.